Comparative cytogenetics of ten species of cichlid fishes (Teleostei, Cichlidae) from the Araguaia River system, Brazil, by conventional cytogenetic methods - Targino Valente, G. [UNESP]; de Andrade Vitorino, C.; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Oliveira, C.; Lima Souza, I.; Martins, C. [UNESP]; Venere, P. C. (Zoological Inst, 2012)
Cichlids represent one of the most species-rich families of fishes and have attracted the attention of evolutionary biologists due to the rapid radiation occurring in some groups and the importance of some species in the world aquaculture. Cytogenetic analysis was conducted in 10 cichlid species from the Araguaia River, Amazon Basin, Brazil. The chromosome number was 2n=48 for all analyzed species except for Laetacara araguaiae Ottoni et Costa, 2009 (2n=44). Chromosomal polymorphism was detected only in Geophagus proximus (Castelnau, 1855), which exhibits an extra large submetacentric and and a dot-like chromosomes. Moreover, the C-banding revealed a general pericentromeric heterochromatic pattern and some additional blocks for some species. The heterochromatic blocks corresponding to AgNOR bearing regions were observed in all species and also corresponded to CMA(3) positive blocks, which were observed in terminal regions. Besides the general conserved chromosomal and heterochromatin patterns for South American cichlids, the presence of GC-rich heterochromatin was quite different in the species Biotodoma cupid (Heckel, 1840), Geophagus proximus, Retroculus lapidifer (Castelnau, 1855), Crenicichla strigata Gunther, 1862 and Heros efasciatus Heckel, 1840. The results suggest that independent events of heterochromatin modification occurred during chromosome evolution in the group, regardless of the conservation of macro-chromosomal structure.
Keywords: chromosome evolution; fish chromosomes; genome; Cichlidae